2016
DOI: 10.1002/bsl.2229
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and Substance Use: Implications for Conditional Release Readiness Evaluations

Abstract: In Foucha v. Louisiana (1992), the United States Supreme Court ruled that individuals adjudicated not guilty by reason of insanity (NGRI) could not remain in a forensic hospital if they were no longer mentally ill and dangerous. Since this decision, a variety of important questions have arisen related to the insanity defense and what should happen to insanity acquittees post-adjudication. This article provides an analysis of clinical issues confronting forensic examiners when psychosis as a result of substance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Given cannabis's popularity, addressing its use for those granted conditional release will continue to warrant resources and treatment. Although research has demonstrated the link between substance abuse and conditional release revocation (Manguno‐Mire et al., 2014; Tabernik & Vitacco, 2016), more research is needed to generate an accurate and up‐to‐date understanding of this complicated relationship.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given cannabis's popularity, addressing its use for those granted conditional release will continue to warrant resources and treatment. Although research has demonstrated the link between substance abuse and conditional release revocation (Manguno‐Mire et al., 2014; Tabernik & Vitacco, 2016), more research is needed to generate an accurate and up‐to‐date understanding of this complicated relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the use of prohibited substances can lead to mental health decompensation, which becomes the underlying reason for revocation (Vitacco et al., 2014). Either way, the use of substances, including cannabis, can lead to an insanity acquittee being revoked and returned to a secure setting (Tabernik & Vitacco, 2016). There is also middle ground that may present the best and most efficient strategy for dealing with substance use violations that do not lead to dangerous behavior.…”
Section: Conditional Release Treatment and Revocationmentioning
confidence: 99%
See 1 more Smart Citation
“…Of studies that included substance abuse, this factor has consistently been associated with failure on conditional release ( Cohen et al, 1988 ; Callahan and Silver, 1998 ; Monson et al, 2001 ; Vitacco et al, 2008 , 2014 ; Green et al, 2014 ). Apart from conditional release of insanity acquittees, substance abuse is one of the strongest predictors of general criminal recidivism among mentally disordered offenders ( Bonta et al, 1998 ) and, together with a history of violence, of future violent behavior ( Swanson, 1994 ; Swanson et al, 2000 ; Douglas and Skeem, 2005 ; Conroy and Murrie, 2007 , Hanson, 2009 , see generally Tabernik and Vitacco, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tabernik and Vitacco postulated several explanations for the association between substance use and failure at conditional release: The association of substance use with forms of criminal conduct, the potential for substance use to exacerbate a mental disorder, and substance use per se can be reason enough to revoke conditional release ( Tabernik and Vitacco, 2016 ). We should add a possible association with medication non-compliance and the potential for substance use alone inducing a mental state that predisposes the individual to criminal conduct or rule violation (e.g., intoxication or substance induced psychotic disorder).…”
Section: Introductionmentioning
confidence: 99%